Effect of Doxycycline on Survival in Abdominal Aortic Aneurysms in a Mouse Model - Adams, Lisa C.; Brangsch, Julia; Kaufmann, Jan O.; Mangarova, Dilyana B.; Moeckel, Jana; Kader, Avan; Buchholz, Rebecca; Karst, Uwe; Botnar, Rene M.; Hamm, Bernd; Makowski, Marcus R.; Keller, Sarah (Contrast Media & Molecular Imaging, 2021)
Background. Currently, there is no reliable nonsurgical treatment for abdominal aortic aneurysm (AAA). This study, therefore, investigates if doxycycline reduces AAA growth and the number of rupture-related deaths in a murine ApoE-/- model of AAA and whether gadofosveset trisodium-based MRI differs between animals with and without doxycycline treatment. Methods. Nine ApoE-/- mice were implanted with osmotic minipumps continuously releasing angiotensin II and treated with doxycycline (30 mg/kg/d) in parallel. After four weeks, MRI was performed at 3T with a clinical dose of the albumin-binding probe gadofosveset (0.03 mmol/kg). Results were compared with previously published wild-type control animals and with previously studied ApoE-/- animals without doxycycline treatment. Differences in mortality were also investigated between these groups. Results. In a previous study, we found that approximately 25% of angiotensin II-infused ApoE-/- mice died, whereas in the present study, only one out of 9 angiotensin II-infused and doxycycline-treated ApoE-/- mice (11.1%) died within 4 weeks. Furthermore, doxycycline-treated ApoE-/- mice showed significantly lower contrast-to-noise (CNR) values (p=0.017) in MRI compared to ApoE-/- mice without doxycycline treatment. In vivo measurements of relative signal enhancement (CNR) correlated significantly with ex vivo measurements of albumin staining (R2 = 0.58). In addition, a strong visual colocalization of albumin-positive areas in the fluorescence albumin staining with gadolinium distribution in LA-ICP-MS was shown. However, no significant difference in aneurysm size was observed after doxycycline treatment. Conclusion. The present experimental in vivo study suggests that doxycycline treatment may reduce rupture-related deaths in AAA by slowing endothelial damage without reversing aneurysm growth.
CRIS-Team Scopus Importer:2023-03-08